EFEKTIFITAS PELAPORAN PENGADAAN BARANG DAN JASA MELALUI APLIKASI SIMONIBARJAS KABUPATEN NIAS PADA SEKRETARIAT DAERAH KABUPATEN NIAS - Kristian Jaya Mendrofa; Maria Magdalena Bate'e; Yosmar Zalukhu; Idarni Harefa (Jurnal Publikasi Manajemen Informatika, 2026)
The phenomenon underlying this research is the ineffectiveness of the centralized AMEL application previously used for procurement reporting at the Regional Secretariat of Nias Regency. Issues such as delays in data presentation, low report accuracy, generalized reporting, and the absence of real-time information made it difficult for leaders to make data-based decisions. In response, the local government developed the SIMONIBARJAS application, a locally based and integrated system designed to provide faster, more detailed, accurate, and real-time reporting. The research problems focus on: (1) the effectiveness of the SIMONIBARJAS application in supporting procurement reporting; (2) the extent to which it addresses AMEL’s weaknesses; (3) users’ perceptions of its ease of use, speed, and reliability; and (4) the role of human resources in supporting its implementation. The findings indicate that SIMONIBARJAS is effective in improving reporting quality by accelerating data presentation, increasing accuracy, providing more detailed reports, and supporting real-time information access for decision-makers. Moreover, inter-unit integration has improved, enabling faster and more accountable decision-making processes. However, challenges remain, including limited user understanding of some features and technical issues such as internet stability, which require further improvement